How does servitization impact inter-organisational structure and relationships of a truck manufacturer's network? - Cakkol, Mehmet (Cranfield University, 2013)
Network relationships play a significant role in the provision of servitized offerings. To date, little empirical research has been conducted to investigate the link between servitization and inter-organisational relationships. The objective of this doctoral thesis is to explore the implications of servitization on a manufacturer’s network. Particular emphasis is placed on the impact on the network structure and relationship attributes. An exploratory in-depth case study was conducted within the truck manufacturing industry using a multi-organisational perspective. An abductive research approach was adopted which was underlined by pragmatism. As part of this approach, 43 interviews were conducted in a total of 11 companies. The findings of the study suggest that managers need to be aware of the different customer needs, related offerings and resultant implications on the network structure and relationships. To this end, the findings show that as the offerings move towards advanced servitized offerings the network becomes more complex in terms of its structure and relationships. The research contributes to the literature by providing a more nuanced description of what actually occurs in a network when a manufacturer provides servitized offerings in conjunction with other product-based offerings. In particular, it identifies the relationship attributes that need to be managed in order to drive the right behaviour for the provision of each of these offerings. Moreover, it is the first known study to uncover triadic as well as tetradic network structures in a servitization context. Equally important, it provides a framework that captures the interplay between the different offerings and the resultant network structure and relationship attributes. In all of these capacities, this research is one of the first known studies to uncover some of the complexities surrounding the way in which inter-organisational relationships are enacted in a servitization context.
© Cranfield University 2013. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner.
Keywords: Servitization; inter-organisational relationships; supply networks; case study